2022
DOI: 10.2196/29621
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smartphone App–Based Psychological Interventions for Reducing Depressive Symptoms in People With Depression: Systematic Literature Review and Meta-analysis of Randomized Controlled Trials

Abstract: Background Depression is a serious, disabling mental disorder that severely affects quality of life. Patients with depression often do not receive adequate treatment. App-based psychotherapy is considered to have great potential to treat depression owing to its reach and easy accessibility. Objective We aim to analyze the impact of app-based psychological interventions for reducing depressive symptoms in people with depression. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 47 publications
6
27
1
Order By: Relevance
“…The results of this systematic review are not consistent with those of Serrano-Ripoll et al (17), who found that app-based interventions resulted in a moderate reduction in depressive symptoms. These authors included in their meta-analysis participants with depressive symptoms, which in some studies had not necessarily been diagnosed by a health professional.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of this systematic review are not consistent with those of Serrano-Ripoll et al (17), who found that app-based interventions resulted in a moderate reduction in depressive symptoms. These authors included in their meta-analysis participants with depressive symptoms, which in some studies had not necessarily been diagnosed by a health professional.…”
Section: Discussioncontrasting
confidence: 99%
“…The fact that within-group improvements in app intervention groups have been observed offers promise for future treatments. Another difference between our systematic review and that of Serrano-Ripoll et al (17) is that our work only involves patients with depressive disorders diagnosed by a health professional. This allows us to ensure that the sample of patients between the different studies is as homogeneous as possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common forms of intervention include using smartphone APP [like PsyCovidApp ( 31 ), Insight Timer Meditation App ( 32 )], videoconferencing ( 33 , 34 ), internet ( 35 , 36 ), and so on. Mobile applications ( 37 ), videoconferencing ( 38 ), text messaging ( 39 ), and social media ( 40 ) have shown to be useful communication methods for delivering mental health services.…”
Section: Discussionmentioning
confidence: 99%